Peru vs. Antarctica: Preliminary Analysis - Ramacciotti de Cubas, Beatriz (1984)
Antarctica, the vast continent of the Southern Hemisphere, already imagined by the Greeks many centuries ago, a region of adventures, explorations and peaceful scientific research, is today of universal concern. Peru's accession to the Antarctic Treaty, in April 1981, signified our country's recognition of the legal regime negotiated and established in Washington in 1959 for the Southern Continent, and in order to glimpse the importance of Peru's action, we first present an overview of the geographic conditions and natural resources of the Antarctic. Then, a synthesis of the historical background (discoveries and explorations) is made, and the main theories that serve as a basis for the sovereignty claims of different states over sectors of the cold continent are also presented. Next, reference is made to the principles of the Antarctic Treaty of 1959, which created a special legal regime for Antarctica, turning it into an immense area of scientific research within a framework of international cooperation, leaving territorial claims frozen for a period of 30 years. But a new period seems to be approaching: on the one hand, the possible revision of the Antarctic Treaty in 1991 is awakening the national interests of the states claiming sovereignty and of other states (Third World) which in world forums (UN) have requested that Antarctica be considered “Common Heritage of Mankind”, and on the other hand, the possibility of the exploitation of the abundant Antarctic resources is generating a growing competition -at official and private levels- among nations and companies, for the economic benefits that would be generated by such exploitation.